Preface - Gerrit Kritzinger (Acta Theologica)
As was the case seven years ago with the publication of Supplementum 2, it is again a privilege for the Bible Society of South Africa to be involved with this volume. In order to fulfil its mission of affordable Bibles to all in their own languages, it remains the ongoing task of the Bible Society to be continuously involved in the process of translating into the languages of South Africa.